Fluorodeoxyglucose-positron emission tomography in carcinoma nasopharynx: Can we predict outcomes and tailor therapy based on postradiotherapy fluorodeoxyglucose-positron emission tomography? - Sarbani Ghosh Laskar; Gunjan Baijal; Venkatesh Rangarajan; Nilendu Purandare; Manju Sengar; Sneha Shah; Tejpal Gupta; Ashwini Budrukkar; Vedang Murthy; Prathamesh S Pai; A K D′Cruz; J P Agarwal (Indian Journal of Medical and Paediatric Oncology)
Background: Positron emission tomography-computed tomography (PET-CT) is an emerging modality for staging and response evaluation in carcinoma nasopharynx. This study was conducted to evaluate the impact of PET-CT in assessing response and outcomes in carcinoma nasopharynx. Materials and Methods: Forty-five patients of nonmetastatic carcinoma nasopharynx who underwent PET-CT for response evaluation at 10-12 weeks posttherapy between 2004 and 2009 were evaluated. Patients were classified as responders (Group A) if there was a complete response on PET-CT or as nonresponders (Group B) if there was any uptake above the background activity. Data regarding demographics, treatment, and outcomes were collected from their records and compared across the Groups A and B. Results: The median age was 41 years. 42 out of 45 (93.3%) patients had WHO Grade 2B disease (undifferentiated squamous carcinoma). 24.4%, 31.1%, 15.6, and 28.8% patients were in American Joint Committee on Cancer Stage IIb, III, Iva, and IVb. All patients were treated with neoadjuvant chemotherapy followed by concomitant chemoradiotherapy. Forty-five patients, 28 (62.2%) were classified as responders, whereas 17 (37.8%) were classified as nonresponders. There was no significant difference in the age, sex, WHO grade, and stage distribution between the groups. Compliance to treatment was comparable across both groups. The median follow-up was 25.3 months (759 days). The disease-free survival (DFS) of the group was 57.3% at 3 years. The DFS at 3 years was 87.3% and 19.7% for Group A and B, respectively (log-rank test, P < 0.001). Univariate and multivariate analysis revealed Groups to be the only significant factor predicting DFS (P value 0.002 and < 0.001, respectively). In Group B, the most common site of disease failure was distant (9, 53%). Conclusion: PET-CT can be used to evaluate response and as a tool to identify patients at higher risk of distant failure. Further, this could be exploited to identify patients who may need treatment intensification. This needs to be validated prospectively.